Breaking cocoa - (:unkn) unknown (Goodwille and Wilson Ltd., Trinidad, 2010)
A picture of labourers on a cocoa estate preparing the cocoa beans for transportation by donkeys to the cocoa houses for drying and fermentation.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Working class--Trinidad and Tobago; Donkeys--Trinidad and Tobago; Cocoa processing--Trinidad and Tobago; Draft animals--Trinidad and Tobago; Cocoa trade--Trinidad and Tobago; 1909